Livelihood and return migration intention among foreign students in the GCC: an interpretative phenomenological analysis - Adewale, Abideen Adeyemi; Omar, Azura (2012)
The indigenous skilled man-power shortfall in the Gulf Cooperation Council (GCC) is a known phenomenon. Efforts at tackling this problem have witnessed policy reforms targeted at human capital development via qualitative education at all levels. In the interim, the GCC countries rely on expatriates to fill the gap. This option may only work in the short term. This may be so given the growth rate of the GCC and the ageing and competition factors vis-à-vis skilled workers from the developed countries. A longer term policy option explored in this paper, and as suggested in some extant migration literature, therefore, is to attract talented students from the Less Developed Countries (LDC), train and retain them as a complement to indigenous skilled man-power. It is presupposed that the initial brain drain this would cause in the sending country would transform to brain gain upon migration return. However, it may be overstretching assumptions that the livelihood opportunities in the host countries align with the aspiration of the foreign students, thereby, making them not to return immediately after their studies. This study presents a phenomenological analysis of the various adjustment issues faced by foreign students in the GCC countries. Elicited by the need to fill an apparent qualitative research gap particularly in the GCC context this study is aimed at unraveling the livelihood strategies of the foreign students and the implications for their return migration intention in their own personal accounts. Data collected via a semi-structured interview are transcribed verbatim, subjected to interpretative phenomenological analysis based on a constant comparative approach, and arranged into themes upon which the results are presented. The themes that emerge in the analysis are discussed in depth and policy recommendations offered